2016
DOI: 10.1063/1.4958583
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat treatment on morphology and crystallinity of electrospun Poly(vinyl alcohol) nanofibers

Abstract: Abstract. Four temperatures of heat treatment had been used (110 ºC, 135 ºC, 150 ºC, and 160 ºC) to give different effects on the morphology of PVA nanofibers. Heat treatment changed the crystallinity of PVA nanofibers which was indicated by the changes of XRD FWHM spectral peaks, and the crystallite size. The changes in the intensity of FTIR spectral transmittance were also observed which might be caused by the differences temperature of heat treatment. The larger crystallite size and the smaller XRD FWHM spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 8 publications
2
11
0
Order By: Relevance
“…In recent studies, DSC crystallinity calculation has largely been used to validate X-ray diffraction (XRD) results [ 40 , 41 ]. The authors' previous study [25] showed that PVA nanofiber has a low degree of crystallinity, and this agrees with XRD results. Low crystalline polymers (amorphous) usually have transparent properties, and the crosslinking of PVA nanofiber mats with the vapor treatment make the nanofibers more transparent due to excessive melting and the plasticizing role of the solvents.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…In recent studies, DSC crystallinity calculation has largely been used to validate X-ray diffraction (XRD) results [ 40 , 41 ]. The authors' previous study [25] showed that PVA nanofiber has a low degree of crystallinity, and this agrees with XRD results. Low crystalline polymers (amorphous) usually have transparent properties, and the crosslinking of PVA nanofiber mats with the vapor treatment make the nanofibers more transparent due to excessive melting and the plasticizing role of the solvents.…”
Section: Resultssupporting
confidence: 85%
“…Many methods have been developed to increase the mechanical strength of nanofiber mats, including changing non-woven fiber mats into self-bundled fiber yarns [17] and reinforcing single nanofibers with other materials [ 18 , 19 , 20 , 21 ], but these methods have been complex and costly. However, one approach is enhancing at junction points in the nanofiber mats by crosslinking fibers together [ 22 , 23 ], and this can be achieved in three ways: first, the mat is heated to a temperature between its glass transition and melting temperature [ 24 , 25 ]; second, the mat is treated with glutaraldehyde (GA) [ 26 , 27 , 28 ], and third, solvent vapor treatment is applied [ 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…From these results, we considered that high temperature and high humidity are the important factors that affect the morphology of CP-F. It has been reported that high temperature can destroy the PVA-based nanofibrous film [ 35 ]. In the present study, the main composition of the nanofibers of CP-F was PVA and PVP and the results revealed that CP-F, after being subjected to high temperatures, became brittle, and the structure of the nanosized fibers was absent.…”
Section: Resultsmentioning
confidence: 99%
“…The partially carbonized fibers formed the grey tone due to the relatively low atomic mass of carbon. It must be noted that the heat treatment could result in the morphology changing of the composite fiber as also indicated in [17]. 4a.…”
Section: Morphology and Compositionmentioning
confidence: 94%
“…The partially carbonized fibers formed the grey tone due to the relatively low atomic mass of carbon. It must be noted that the heat treatment could result in the morphology changing of the composite fiber as also indicated in [17]. Energy Dispersive Spectrum (EDS) of X-ray diffraction spot analysis was used to identify the elemental composition of the selected locations.…”
Section: Morphology and Compositionmentioning
confidence: 99%